Penatalaksanaan Holistik pada Lansia dengan Isolated Systolic Hypertension (ISH), Suspek Retinopati Hipertensi dan Imobilitas: Penatalaksanaan Holistik pada Lansia dengan Isolated Systolic Hypertension (ISH), Suspek Retinopati Hipertensi dan Imobilitas - Karimah Khitami Aziz; Dian Isti Angraini (Medula, 2021)
Isolated Systolic Hypertension (ISH) is an increase of systolic blood pressure (BP) without diastolic BP common in old age. ISH may develop from a history of chronic essential hypertension or result from arterial stiffness in normotensive person. Secondary causes of arterial stiffness are type 1 diabetes, osteoporosis with calcification, atherosclerosis, peripheral vascular disease, thyrotoxicosis and aortic disorders. Implementation of family medicine and evidence based medicine by identifying risk factors, clinical problems and management based on a patient centered and family approach. This study is a case report. Primary data were obtained through history taking, physical examination and home visit. The assessment based on the holistic initial diagnosis, process and final diagnosis by in-depth interviews, observation and notes. The patient complained of intermittent headaches and blurred vision since 1 week ago. Complaints for the first time and never been treated. The patient's concern with the complaint interferes with his activities and rest. The patient's expectation of complaints is reduced and not worsen. Patients' perceptions of complaints occur due to certain lifestyles causing diseases that are not known for sure by patient and their family. The patient was diagnosed with grade II ISH. The patient's father had history of hypertension and heart disease. The patient's treatment pattern is curative, rarely has light physical activity, lack of knowledge about the disease, inappropriate diet and eating habits, elderly age and lack of family knowledge about the disease and its complications. Functional degree 2. After the intervention shows clinical improvement and changes in behavior. ISH in the elderly with insufficient knowledge about risk factors, drug use and adherence to BP control can cause acute and advanced complications.